Thinking Mathematically (6th Edition)

Published by Pearson
ISBN 10: 0321867327
ISBN 13: 978-0-32186-732-2

Chapter 6 - Algebra: Equations and Inequalities - 6.1 Algebraic Expressions and Formulas - Exercise Set 6.1: 58

Answer

-5$x^{2}$ + 3x

Work Step by Step

2(-5$x^{2}$ + 3x) - (3x - 5$x^{2}$) Use the distributive property to remove the parentheses =2.-5$x^{2}$ + 2.3x - (3x - 5$x^{2}$) Drop parentheses and change the sign of each term in parentheses: - (3x - 5$x^{2}$) = - 3x + 5$x^{2}$ = 2.-5$x^{2}$ + 2.3x - 3x + 5$x^{2}$ Multiply = -10$x^{2}$ + 6x - 3x + 5$x^{2}$ Group like terms = (-10$x^{2}$ + 5$x^{2}$) + ( 6x - 3x ) combine like terms (-10$x^{2}$ + 5$x^{2}$) = (-10+5)$x^{2}$ = -5$x^{2}$, (6x - 3x) =(6-3)x = 3x =-5$x^{2}$ + 3x
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.